Impact of pile head restraint and soil stiffness on the response of steel piles for integral abutment bridges - Almar, Sofie; Binbach, Lydia (My University, 2026)
Integral abutment bridges are commonly designed using simplified pile models where the pile is treated as an isolated structural element with a free pile head. To better represent the actual structural behaviour, global buckling analysis can be used as an alternative modelling approach, where stabilisation from the surrounding soil and the integrated bridge system is considered. The purpose of this study is therefore to evaluate whether alternative modelling approaches can provide a more realistic estimation of axial pile capacity in integral abutment bridges. The study combines literature review, case study and finite element modelling. A finite element model was developed in BRIGADE/Plus and verified against hand calculations using simplified single pile models. The analyses were gradually ex tended to include soil resistance, transverse loading, and different boundary condi tions. Both single piles and piles integrated into the bridge system were analysed under two different soil conditions to evaluate force distribution, bending moments, buckling behaviour, and pile capacity. The results show significant differences in structural behaviour depending on soil conditions and model assumptions. The piles embedded in friction soil developed a higher axial capacity than the piles surrounded by soft clay. Compared with the isolated pile models, the piles integrated into the bridge system generally exhibited an increased capacity due to redistribution of internal forces and the sequential for mation of plastic hinges. The results also indicate that simplified assumptions with free pile heads may underestimate the stabilising effect provided by the surrounding structural system. The study demonstrates that modelling assumptions regarding soil stiffness and pile restraint significantly influence the predicted pile capacity in integral abutment bridges. Simplified single pile models may therefore underestimate the structural capacity of piles interacting with the bridge system. The results indicate that soil structure interaction and restrained pile behaviour should be considered in non linear analyses of integral abutment bridges, particularly when evaluating ultimate limit states and buckling behaviour.
Keywords: Integral abutment bridge, structural behaviour